2017
DOI: 10.1152/japplphysiol.00533.2017
|View full text |Cite
|
Sign up to set email alerts
|

Single passive leg movement assessment of vascular function: contribution of nitric oxide

Abstract: Broxterman RM, Trinity JD, Gifford JR, Kwon OS, Kithas AC, Hydren JR, Nelson AD, Morgan DE, Jessop JE, Bledsoe AD, Richardson RS. Single passive leg movement assessment of vascular function: contribution of nitric oxide. J Appl Physiol 123: 1468-1476, 2017. First published August 31, 2017; doi:10.1152/japplphysiol.00533.2017.-The assessment of passive leg movement (PLM)-induced leg blood flow (LBF) and vascular conductance (LVC) is a novel approach to assess vascular function that has recently been simplified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…This lack of significant differences adds confidence to the current approach of calculating DFA BF in the present investigation. It should also be noted that the current values for baseline CFA and SFA BF are similar to those previously recorded in the literature (Broxterman et al., ; Holland, Brown, Scoutt, & Taylor, ; McDaniel et al., ; Trinity et al., ; Zuj, Prince, Hughson, & Peterson, ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This lack of significant differences adds confidence to the current approach of calculating DFA BF in the present investigation. It should also be noted that the current values for baseline CFA and SFA BF are similar to those previously recorded in the literature (Broxterman et al., ; Holland, Brown, Scoutt, & Taylor, ; McDaniel et al., ; Trinity et al., ; Zuj, Prince, Hughson, & Peterson, ).…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, PLM‐induced hyperaemia is attenuated in ageing and disease, but the effect of cuff occlusion on these results has yet to be determined (Groot et al., ; Trinity et al., ; Witman et al., ). Furthermore, intra‐arterial drug infusion studies, aiming to further quantify the contribution of particular vasodilators to the PLM‐induced hyperaemic response, regularly utilize an occlusion cuff placed just below the knee to localize the effects of a drug to the upper leg (Broxterman et al., ; Trinity et al., ; Trinity et al., ). For instance, Trinity et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the blood sample collection, participants were placed in an upright-seated position, near-infrared spectroscopy (NIRS) probes were set on both vastus lateralis and subjects were left at rest in this position for 10 minutes. Subsequently, the single passive leg movement (sPLM) test was performed on one leg, and after 10 minutes rest the test was performed on the other leg [15]. All measurements taken in both right and left limbs were then averaged.…”
Section: Study Overviewmentioning
confidence: 99%
“…Recent investigations have revealed that sPLM-induced hyperemia is predominantly a consequence of NO-mediated vasodilation [15]. Therefore, we have adopted this noninvasive and reliable method to determine NO bioavailability [15,16]. During the test, the subjects rested in the upright-seated position for 10 min before the start of data collection and remained in this position throughout this part of the study.…”
Section: No-bioavailability Via Splmmentioning
confidence: 99%